Deceased organ donation efficiency in Switzerland from 2014 to 2023 compared to other European countries according to the Donor Conversion Index (DCI) – an ecological study (Swiss Medical Weekly, 2025)
AIMS OF THE STUDY: Deceased donation activity is typically calculated as the number of donors per year per million people (pmp) and is referred to as the donation rate. To assess donation efficiency rather than donation activity, concepts such as the Donor Conversion Index (DCI) consider that not every death is eligible for organ donation. These are primarily deaths resulting from diseases associated with potentially devastating cerebral injury leading to brain death. We present the 2014–2023 evolution of the deceased donation activity and efficiency in Switzerland compared with selected European countries. How does Switzerland perform when organ donation programmes are evaluated using the DCI instead of the donation rate? The results are discussed in the context of implemented measures in Switzerland to increase organ donation activity.METHODS: We calculated the DCI (number of donors divided by the number of eligible deaths, multiplied by 100), donation rate (number of donors divided by the number of residents, multiplied by 106), and mortality rate (number of eligible deaths divided by the number of residents, multiplied by 105) for each country and year using population-based data from the Global Observatory on Donation and Transplantation (GODT) and Eurostat. Eligible deaths for deceased organ donation include deaths from diseases associated with potentially devastating cerebral injury related to brain death, as defined by selected ICD-10 codes suggested by the European Directorate for the Quality of Medicines & Healthcare. We present trends for the years 2014–2023 for all three indicators and compare the results of Switzerland with those of seven European countries (Austria, France, Germany, Italy, the Netherlands, Spain, and the United Kingdom).RESULTS: Over the 10-year study period, efficiency, as measured by the DCI, increased by 2–72% in all countries. In Switzerland, the DCI rose from 3.2 donors per 100 eligible deaths in 2014 to 5.5 donors per 100 eligible deaths in 2023, representing the largest increase in efficiency among the countries analysed (+2.3 donors per 100 eligible deaths, or +72%). The primary driver of Switzerland’s improved donation efficiency was increased donations after circulatory determination of death (DCD) since 2016. The DCI offers a different perspective on donation activity compared with the donation rate expressed in pmp. The upward trend over the past decade in the countries analysed is less pronounced for the donation rate than for the DCI. This divergence is accompanied by a declining mortality rate of diseases eligible for donation during the period studied. At the end of the study period, Switzerland's total DCI ranked second among the countries analysed, following Spain, while its donation rate in pmp ranked fourth, following Italy and France. Among the countries analysed, Switzerland had the lowest mortality rate of diseases eligible for organ donation throughout the study period.CONCLUSIONS: Despite declining next-of-kin consent rates, Switzerland's organ donation programme is among the most efficient in Europe, according to the DCI. If consent matched that of other countries, efficiency could be even higher. The increase in the DCI from 2014 to 2023 suggests that measures to increase organ donation rates in Switzerland may have been effective. Swiss emergency and intensive care staff appear to appropriately identify, refer, and manage potential deceased organ donors. When comparing trends in organ donation figures between countries, it is important to consider differences in mortality due to eligible diseases associated with potentially devastating cerebral injury leading to brain death.